2015
DOI: 10.1186/s13104-015-1487-z
|View full text |Cite
|
Sign up to set email alerts
|

Tools for translational epigenetic studies involving formalin-fixed paraffin-embedded human tissue: applying the Infinium HumanMethyation450 Beadchip assay to large population-based studies

Abstract: BackgroundLarge population-based translational epigenetic studies are emerging due to recent technological advances that have made molecular analyses possible. For example, the Infinium HumanMethylation450 Beadchip (HM450K) has enabled studies of genome-wide methylation on a scale not previously possible. However, application of the HM450K to DNA extracted from formalin-fixed paraffin-embedded (FFPE) tumour material has been more challenging than application to high quality DNA extracted from blood. To facili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…The identified tumor-enriched tissue was macrodissected from between two to ten Methyl Green stained sections per tumor using both a scalpel (Swann-Morton, Sheffield, England) and a 21-guage syringe needle (Terumo, Tokyo, Japan), as previously described [28]. DNA was extracted using the QIAamp DNA FFPE Tissue Kit as per the manufacturer’s protocol (Qiagen; Hilden, Germany), varied only by an extended tissue incubation time of 48 hours with 20μl of Proteinase K (20mg/ml) replenished at 0 and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…The identified tumor-enriched tissue was macrodissected from between two to ten Methyl Green stained sections per tumor using both a scalpel (Swann-Morton, Sheffield, England) and a 21-guage syringe needle (Terumo, Tokyo, Japan), as previously described [28]. DNA was extracted using the QIAamp DNA FFPE Tissue Kit as per the manufacturer’s protocol (Qiagen; Hilden, Germany), varied only by an extended tissue incubation time of 48 hours with 20μl of Proteinase K (20mg/ml) replenished at 0 and 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…Our training cohort consisted of 35 PGC samples and 13 RGC samples which were analyzed using the Infinium HumanMethylation450 Beadchip assay which allows the assessment of the methylation status of over 450,000 CpGs throughout the genome. The Infinium HumanMethyla-tion450 Beadchip assay (Illumina, San Diego, CA, USA) was performed in the Johns Hopkins University DNA Microarray Core according to the manufacturer's instructions specific for formalin-fixed embedded material [27]. Locus methylation was calculated as a β value using GenomeStudio software with the low to high ranging from 0 to 1, respectively.…”
Section: Infinium Humanmethylation450 Beadchip Assaymentioning
confidence: 99%
“…39,40 Our experience with the Infinium HumanMethylation450 BeadChip array, which has been validated using TCGA data, showed that the CpG island (Chromosome17: 41278135-41278459) is highly methylated in blood-derived DNA from both affected and unaffected women and lacks variability between individuals. 41,42 Therefore, DNA methylation assessment of this invariant region is likely to be uninformative and, indeed, no differences in BRCA1 DNA methylation levels were observed in this region between cases and controls irrespective of their BRCA1 or BRCA2 mutation status. 39,40 Ziller et al 43 found that DNA methylation levels across the intermediate and low CpG density promoters and transcription start sites, rather than the CpG islands, are dynamic and variable between individuals.…”
Section: Dna Methylation: Methodology and Measurementmentioning
confidence: 99%